Systematic Literature Review: Implementation of Dispute Settlement Methods Between Trade Unions and Companies in Indonesia - Oktafien, Shinta; Sofiati, Evi; Kowara, Yadhi; Permana, Jajang; Endang, Cucu; Hidayat, Teddy; Ahmadien, Iskandar; Sumadinata, Yelli Eka; Tiarapuspa, Tiarapuspa; Aseanty, Deasy (Green Publisher Indonesia, 2023)
Sometimes the working relationship established between employers and workers or trade unions can run well. Sometimes differences in goals or interests owned by the two parties can cause conflicts or disputes that, if the organization or company cannot handle them properly, will harm the sustainability of the business undertaken by the organization. Therefore, it is necessary to have an industrial relations dispute resolution mechanism that can be done in two ways: through litigation (court) and non-litigation (outside the court). This study aims to provide a pattern of research overview with the theme of industrial relations dispute resolution with data obtained from several reputable international/national journals published between 2017 to 2023. The research method used, namely in the Systematic Literature Review (SLR) Method, is useful in identifying, reviewing, evaluating, and interpreting many studies obtained with research topics or themes that attract attention, as well as with certain relevant research questions. The results showed that the dominant platform used in research on the theme of industrial relations dispute resolution is the settlement mechanism and the role of trade unions in resolving labour relations disputes.